Water treatment using slow sand filter - Aimi Fadlini, Fauzi (2010)
Studies about the slow sand filtration treats any type of water to see the efficiency of the treatment performance (consist of 3 layers of fine sand <600.1m, 6001.tm, im, activated carbon, varies size of river gravel). The purpose of purifying water is to increase the quality of water that is safe and no harm for human consumptions. The capability of slow sand filter is known as the most efficient water treatment method base on previous nineteenth century practical used by using the slow sand filtration method. It is cheapest method comparing to other kind of water treatment, not to say that other treatment is not functional but instead it is the cheapest and less maintenance required so it is most common used method in developing countries and small community on producing a good quality of treated water that are safe and cheap. The removal of total suspended solids (TSS), color, turbidity, toxic heavy metals iron, biological oxygen demand (BOD) and chemical oxygen demand (COD), E-coli, were evaluated for water treatment. For 4 weeks slow sand filter filtered untreated water from sungai Belat, successfully reduces the concentration of physical parameters up to 85% of losses, for chemical parameters and Iron reduces is 11% until 35% of losses.SSF need further filtration to increase the potential of filtration.